1996
DOI: 10.1080/00207549608904960
|View full text |Cite
|
Sign up to set email alerts
|

A new grouping measure for evaluation of machine-component matrices

Abstract: The machine-component matrix is the main input to most machine-component grouping models med in cellular manufacturing. A number of measures have been developed for performance evaluation of rnachinc-(:omponent grouping algo rithms. In this paper, the relationship between these measures and the performance of the corresponding cellular manufacturing system is evaluated and a new grouping measure is developed which is more consistent in predicting the suitability of a manufacturing system for cellular manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…La evaluación de desempeño se realizó con tres problemas de prueba: el primero poseía 5 máquinas y 7 partes, tal como fue presentado por Vitanov et al (2008) (Tabla 1); el segundo poseía 7 máquinas y 11 partes, tal como fue presentado por Seifoddini & Djassemi (1996) (Tabla 3); y el último, poseía 14 máquinas y 24 partes, tal como fue presentado por King (1980) (Tabla 4). …”
Section: Nsga2unclassified
“…La evaluación de desempeño se realizó con tres problemas de prueba: el primero poseía 5 máquinas y 7 partes, tal como fue presentado por Vitanov et al (2008) (Tabla 1); el segundo poseía 7 máquinas y 11 partes, tal como fue presentado por Seifoddini & Djassemi (1996) (Tabla 3); y el último, poseía 14 máquinas y 24 partes, tal como fue presentado por King (1980) (Tabla 4). …”
Section: Nsga2unclassified
“…Cada una de las soluciones se representa en un cromosoma, en el cual la primera parte corresponde a un vector que contiene la agrupación de las máquinas, a continuación la agrupación de las partes, luego la cantidad de celdas o familias de partes y, finalmente, los límites en las posiciones de las permutaciones de las máquinas y partes para conformar las celdas y familias como se muestra en las Matriz de incidencia 7x11 Seifodini y Djassemi [20] Matriz de incidencia 14x24 King [21] Matriz de incidencia 35x20 Burbidge [22] Matriz de incidencia 24x40 Chandrasekharan y Rajagopalan [23] Tabla 1. Problemas de prueba de distribución de planta de celdas de manufactura.…”
Section: Codificación De Las Solucionesunclassified
“…Therefore, the more close the 1s are, the larger the bond energy measure will be. Hsu (1990) showed that neither group efficiency nor group efficacy is consistent in predicting the performance of a cellular manufacturing system based on the structure of the corresponding machine-part matrix (Seifoddini & Djassemi, 1996). Hsu (1990) considered the GCI as follows:…”
Section: Bond Energy Measure (Bem)mentioning
confidence: 99%